Miles Franklin Literary Award. - The Trust Company ([Australia] : The Trust Company, 2011)
"The Miles Franklin Award has a history almost as colourful as Miles Franklin herself. Like any institution that has been around for over 50 years, the Award has attracted great praise and affection - but also some comments and criticism. Have you ever wondered who the first (or the 12th or the 35th) winner of the Award was? How are the judges chosen? How do they pick the best book from so many contenders? And does it have to be by an Australian writer? These questions - and more - answered here."
Title from title screen (viewed on 21 May 2013)
Mode of access: Available online. Address as at 4/12/2013
Selected for archiving
Keywords: Australian literature -- Awards; Literary prizes -- Australia; Australian